Africanised public administration sold out public service delivery : a case of South Africa - Kgobe, F. K. L. (International Conference on Public Administration and Development Alternative (IPADA), 2020)
This paper argues that in as far as service delivery legislation for combating corruption and maladministration is concerned the administration of public services is contaminated with bad practices. Local government is currently viewed as a place where corruption is being decentralised as it is not only in the national government realm where it occurs only. In this article corruption serves as a pipeline of selling out service delivery in the local government. People love the ANC led government, but it keeps on disappointing them with poor service delivery. Lack of complacency to legislation is a major debacle faced by the ruling party. Basic principles and values governing public administration are fulcrum to serve as a panacea. The debacle is that South Africa has many great legislative frameworks lamenting on how services delivery should be carried out. It is extremely shocking to see maladministration perpetuating even when measures and institutions of democracy are put in place. There is a huge gap between policy formulation and implementation. The institutions and bodies of government regulating public service delivery will be critically examined to check its fitting in the current juncture of public administration. Wrongdoings in the public administration practices are perceived to be normal so such conduct is tainting and reducing the capacity of public administration machineries to provide economic, efficient, and effective service delivery that is in line with Batho Pele principles. The paper is purely conceptual, and a desktop study which relied heavily on literature review to underpin the argument. The paper takes cognisance of section 195 of the Constitution of the Republic of South Africa, 1996 to extract and expantiate the argument. The paper argues that Africanised public administration must be indebted to Christian doctrine. It recommends a move from reconciliation to justice taking place by bringing those at the forefront of Africanised public administration to the rule of law, which compromises the quality of public service delivery. The paper further recommends that measures in public administration machineries should be reinforced. Having cases of corruption in local government that are left without justice taking place is signaling that public service delivery has been sold out.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Constitution; Dichotomy; Public administration; Protests; Service delivery; Public adminstration -- South Africa; Local government -- South Africa